Development of Teaching Material for Narrative Writing Using Graphic Organizer Story Map in Elementary School - Ramona Kurnia; Darnies Arief; Irdamurni Irdamurni (Fakultas Ilmu Pendidikan UNP)
Most of materials used in narrative writing are not interested and not related to the writing process (pre-writing, when writing, and post writing). Our goal is to measure the effectiveness, practicality, and validity of the narrative writing material namely Graphic Organizer Story Map. We are doing research and development. We used 4-D model which consists of 4 stages: define, design, develop and disseminate. The validity test is obtained through the learning plan sheet on implementation, and the assessment of teachers and students responses. The effectiveness is obtained from activity, process assessment and result of narrative writing. We conducted an evaluation and obtained the “very valid”, “very simple” and “very effective”. We found the enhancement number of student who meet the passing grade on narrative writing. The teaching material for narrative writing with using Graphical Organizer Story Map is valid, simple and effective to use.